Exploring the mechanism of enterotoxicity mediated by the microbiome-butyrate-PPAR axis in podophyllotoxin through the toxicological evidence chain (TEC) concept - Duan, Jiajia; Du, Peipei; Jiang, Tao; Ma, Xiao; Sun, Jiaxing; Liang, Jin; Wang, Jingjing; Liu, Chuanxin (Ecotoxicology and environmental safety, 2024)
Podophyllotoxin (PPT) is a lignan derived from the roots and stems of the Podophyllum plant. However, its enterotoxicity restricts its clinical application. The underlying mechanisms by which PPT exerts its action remain largely elusive. This study aimed to evaluate the molecular mechanisms underlying PPT-induced enterotoxicity utilizing the concept of toxicological evidence chain. Changes in body weight, behavior, and histopathological and biochemical markers in rats were observed. Additionally, microbiome, metabolome, and transcriptome analyses were integrated to identify potential microorganisms, metabolic markers, and major pathways using a co-occurrence network. Our findings suggested that PPT induced pathological changes in rats, including weight loss, diarrhea, and inflammation accompanied by increased levels of IFN-γ, IL-5, IL-6, GRO/KC, and IL-12p70. The decrease in butyrate levels in the PPT group may be related to the enrichment of Firmicutes. The reduction of butyrate levels may impair the expression of PPARγ, subsequently promoting Escherichia-Shigella proliferation. Additionally, the suppression of PPARs pathway may result in the increased production of inflammatory factors, contributing to enterotoxicity. This study offers a novel understanding of the molecular mechanisms underlying PPT-induced enterotoxicity, making a significant contribution to developing strategies to mitigate PPT toxicity and prevent associated diseases. [Display omitted] •The enterotoxicity of Podophyllotoxin limits its clinical use.•Podophyllotoxin altered the gut microbial composition of rats.•The PPAR pathway is highly associated with the enterotoxicity.